Socioeconomic implications of global oil depletion for South Africa : vulnerabilities, impacts and transition to sustainability - Wakeford, Jeremy J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.